LA IGLESIA Y LA REPRESIÓN EN LA GUERRA CIVIL ESPAÑOLA - RAGUER SUÑER, HILARI (Universidad Nacional del Litoral, 2017)
The terrible religious persecution in the republican area had an understandable echo in Rome. But, at the beginning, the Vatican’s attitude was very reticent because the result was uncertain and also for the fear to the Fascist’ influence and, mainly, the Nazism. The first public taking of a post was the speech of Pope Pius XII in Castelgandolfo on 14th September 1936. The Vatican took around two years before recognising thoroughly General Franco, and they did it for being realists, he was winning. The Spanish bishops, despite they had wished the military coup, they hadn’t joined to the conspiracy. They supported it a posteriori. Their most important taking of a post was a collective letter to the worldwide episcopate, on 1st July 1937. They disagreed with any of the efforts for an international mediation and a negotiated peace. They rejected to recognize the Franco’s repression. The Spanish Church should ask for forgiveness.